Evaluation of two W‐band power dividers in a subwavelength dielectric fibre technology. Issue 16 (1st August 2016) - Reese, R.; Jost, M.; Jakoby, R.
Abstract : The design and characterisation of two different power divider techniques, i.e. Y‐branch and multimodal power dividers, based on subwavelength dielectric fibre technology is presented. Both have been successfully established in the optical domain for dielectric waveguides and are adapted to W‐band frequencies (75–110 GHz). Both power dividers are made out of the cross‐linked polystyrene Rexolite 1422 and have been processed by milling. Simulations predicted insertion losses between 3.5 and 4 dB while the electrical characterisation showed insertion losses between 3.5 and 5 dB. The multimodal power divider has the best performance with 1–1.5 dB lower insertion losses compared with the Y‐branch divider.